Multiculturalism in East Asia a transnational exploration of Japan, South Korea and Taiwan - Iwabuchi, Koichi 1960-; Kim, Hyun Mee; Hsia, Hsiao-Chuan (London Rowman & Littlefield International, 2016)
"An examination of multiculturalism in East Asia using a transnational approach. The collection focuses in on Japan, Korea and Taiwan to examine key issues including policy, racial discourse, subjectivity and the implications for established ethic minority communities"--Provided by publisher.
Rethinking multiculturalism from a trans-East Asian perspective / Koichi Iwabuchi, Kim Hyun Mee, Hsiao-Chuan Hsia -- Section 1. Multiculturalism policy discourse : critical interrogation -- Korean multiculturalism and its discontents / Ji-Hyun Ahn -- Multicultural Taiwan : policy developments and challenges / Li-Jung Wang -- Multicultural co-living (tabunka kyosei) in Japan : localized engagement without multiculturalism / Koichi Iwabuchi -- Section 2. Racialization of multicultural situations -- The racialization of multicultural families by media in a multicultural nation / Jung Hyesil -- Legislating race and the nation in Taiwan : how immigration laws embodies the dark side in the nation-building process / Bruce Yuan-Hao Liao -- Intersecting Japanese nationalism and racism as everyday practices : toward constructing a multiculturalist Japanese society / Yuko Kawai -- Section 3. Cultural politics of multicultural subject makings -- Can "multicultural soldiers" serve the nation? : the social debate about the military service management of mixed-race draftees in South Korea / Kim, Hyun Mee -- The making of multiculturalistic subjectivity : the case of marriage migrants' empowerment in Taiwan / Hsiao-Chuan Hsia -- Historicizing mixed-race representations in Japan : from politicization to identity formation / Sachiko Horiguchi and Yuki Imoto -- Section 4. Multiculturalism and long-existing ethnic minorities -- Hwagyo under the multiculturalism in South Korea : residual Chinese or emerging transcultural subject? / Shin Hyunjoon -- Multiculturalism and indigenous peoples : a critical review of the experience in Taiwan / Kuan, Da-Wei -- Living in love and hate : transforming representations and identities of Zainichi Koreans in contemporary Japan / Kohei Kawabata.
Includes bibliographical references and index.
Keywords: Multiculturalism -- East Asia; Multiculturalism -- Japan; Multiculturalism -- Korea (South); Multiculturalism -- Taiwan; Transnationalism -- Social aspects -- East Asia; Minorities -- Government policy -- East Asia; East Asia -- Ethnic relations -- Government policy; Japan -- Ethnic relations -- Government policy; Korea (South) -- Ethnic relations -- Government policy; Taiwan -- Ethnic relations -- Government policy